The role of a second RGD motif in the ID protein of a Namibian SATI foot-and-mouth disease virus for target cell attachment - Van Rensburg, H.G. (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2007.